The Middle School Syndrome - Gibson, Huston J. (My University, 2014)
This manuscript explores the notion of the middle. Whether discussing birth order, cars, housing, or schools, first and last seems to overshadow the middle. In particular, when investigating K-12 public schools and their relationship to housing prices, a “Middle School Syndrome” was uncovered.
Keywords: Middle School Syndrome; Notion of the middle; K-12 public schools; Housing prices